Big data implementation for agriculture commodity knowledge management - Eni Kustanti (Jurnal Pustakawan Indonesia, 2021)
Big data in the era of the industrial revolution can be an important source of information in various fields including agriculture. Agricultural commodity data from upstream to downstream becomes important information that will become knowledge in increasing productivity. Knowledge management can be an option in managing various agricultural commodity information. This study aims to describe the big data of agriculture which is the source of knowledge management in agricultural commodities. Agricultural commodities that can be managed big data in accordance with the Echelon I unit that oversees it can be in the form of food crops, horticultural crops, livestock and plantations. Bigdata management requires technology support and human resources management. Through knowledge management of agricultural commodities, various knowledge both tacit and explicit from within the institution itself will be well documented and beneficial to the institution. The implementation of knowledge management for agricultural commodities will go through a process of creating, storing knowledge, sharing knowledge and applying knowledge. The implementation of knowledge management must be supported by human resources (people), processes (processes) and technology (technology). Through the implementation of knowledge management in agricultural commodities will increase the role of libraries within the Indonesian Ministry of Agriculture in supporting agricultural development. If so far the role of the library has not been taken into account, through knowledge management will become a reference in the development of agricultural commodities.